2000
DOI: 10.1248/cpb.48.1310
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationship of Orally Potent Tripeptide-Based HIV Protease Inhibitors Containing Hydroxymethylcarbonyl Isostere.

Abstract: We designed and synthesized a new class of peptidomimetic human immunodeficiency virus protease inhibitors containing a unique unnatural amino acid, allophenylnorstatine [Apns; (2S,3S)-3-amino-2-hydroxy-4-phenylbutyric acid], with a hydroxymethylcarbonyl isostere as the active moiety. From a structure-activity relationship study of HIV-1 protease inhibition, enzyme selectivity for other aspartyl proteases, the antiviral activity and pharmacokinetics in rats, 24c (KNI-227) and 24d (KNI-272, our first clinical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 0 publications
0
37
0
1
Order By: Relevance
“…6 -11 These inhibitors contain an ␣-hydroxy-␤-amino acid residue, allophenylnorstatine [Apns, (2S, 3S)-3-amino-2-hydroxy-4-phenylbutanoic acid], which has a hydroxymethylcarbonyl (HMC) isostere derived from a natural scissile amino acid sequence "Phe-Pro." [12][13][14][15][16][17][18][19][20] As depicted in Figures 1B and C, these "O-N intramolecular acyl migration"-type water-soluble prodrugs of HIV-1 protease inhibitors, which are O-acyl isoforms of the parent drugs, increase water solubility and are easily converted to the corresponding N-acyl forms, i.e., parent drugs via O-N intramolecular acyl migration. This migration can be precisely controlled by pH and is completed in a short time with no side reactions under physiological conditions (pH 7.4).…”
Section: Introductionmentioning
confidence: 99%
“…6 -11 These inhibitors contain an ␣-hydroxy-␤-amino acid residue, allophenylnorstatine [Apns, (2S, 3S)-3-amino-2-hydroxy-4-phenylbutanoic acid], which has a hydroxymethylcarbonyl (HMC) isostere derived from a natural scissile amino acid sequence "Phe-Pro." [12][13][14][15][16][17][18][19][20] As depicted in Figures 1B and C, these "O-N intramolecular acyl migration"-type water-soluble prodrugs of HIV-1 protease inhibitors, which are O-acyl isoforms of the parent drugs, increase water solubility and are easily converted to the corresponding N-acyl forms, i.e., parent drugs via O-N intramolecular acyl migration. This migration can be precisely controlled by pH and is completed in a short time with no side reactions under physiological conditions (pH 7.4).…”
Section: Introductionmentioning
confidence: 99%
“…4. Although KNI-272 showed good oral bioavailability in a human clinical trial, the plasma half-life was very short (t 1/2b = 23 min, intravenous), which suggested that the inhibitor must be further optimized for a more desirable pharmacokinetic profile [24].…”
Section: Hiv Protease Inhibitorsmentioning
confidence: 99%
“…This observation suggested that the P2-P29 residues form the pharmacophore of the inhibitor. As a result, we opted to discard the P2-cap moiety and altered the design of the P2 residue to a P1-cap moiety [24]. According to an extensive literature search, a variety of ligands optimized for binding to the S2 subsite of HIV protease had been reported for hydroxyethylamine inhibitors, namely 2,6-dimethylphenoxyacetyl and 3-hydroxy-2-methylbenzoyl groups.…”
Section: Hiv Protease Inhibitorsmentioning
confidence: 99%
“…Das Norstatinisoster 3 (Schema 1) wurde als eine erste Zielstruktur unserer Studien ausgewählt, da es eine Klasse potenter Inhibitoren der Metallo-und Aspartylproteasen repräsentiert. [11,12] Das Polystyrolgebundene Triphenylphosphanderivat 4 (Schema 2, 1.2 mmol g À1 ) ist ein klassisches polymeres Reagens, [13,14] das routinemäßig in polymerunterstützten Halogenierungen, Mitsunobu-und Wittig-Reaktionen Anwendung findet. [14,15] Unserer Kenntnis nach ist dies der erste Bericht über die …”
unclassified